Towards a new Methodological Approach. Roman Law Community in Lviv Since Mid-19th Century until Early 20th Century - Nancka, Grzegorz (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The aim of this article is to present the methodological views of Lviv-based scholars such as: Józafat Zielonacki, Ferdynand Źródłowski, Leonard Piętak, Leon Piniński, Marceli Chlamtacz and Ignacy Koschembahr-Łyskowski. In the 19th century German science of law, a special role was played by the so-called Pandectism. In the second half of the 19th century, the Pandectist thought permeated to other countries, including Austria. It also reached the Lviv Roman law community and found its representatives there. As time went by, before the end of the 19th century, it turned out that Pandectism was gradually exhausting its possibilities, and so the search for new research methods began. This article is intended to illustrate until which point in time the Roman law community in Lviv presented the Pandectist point of view and when it started to depart from it.